PREVALENCE OF OBESITY AND ITS PREVENTION - H.Q. Ruzmatova (Scholar Express Journals, 2024)
During the process of evolution, the human body adapted to store nutrients during times of abundance to ensure energy supply during scarcity or forced fasting. This evolutionary advantage enabled humans to survive. In ancient times, obesity was considered a sign of prosperity, sufficiency, fertility, and health. Unfortunately, today obesity is recognized as a significant risk factor for numerous diseases.
Keywords: Obesity; Metabolic syndrome